2005
DOI: 10.1103/physreva.72.063407
|View full text |Cite
|
Sign up to set email alerts
|

Effective spin quantum phases in systems of trapped ions

Abstract: A system of trapped ions under the action of off-resonant standing-waves can be used to simulate a variety of quantum spin models. In this work, we describe theoretically quantum phases that can be observed in the simplest realization of this idea: quantum Ising and XY models. Our numerical calculations with the Density Matrix Renormalization Group method show that experiments with ion traps should allow one to access general properties of quantum critical systems. On the other hand, ion trap quantum spin mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
240
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(266 citation statements)
references
References 30 publications
(55 reference statements)
22
240
0
1
Order By: Relevance
“…More subtly, we find that in the presence of the dipolar interactions an algebraic tail is visible in the long-distance decay of correlation functions even in the gapped phase. A similar effect has been reported previously for Ising systems with dipolar interactions [62,63], for longrange interacting p-wave superconductors with Majorana edge modes [64], and for systems with quadratic algebraically decaying interactions it can be proven that in such systems the correlation functions decay with the same exponent as the one of the interaction [65]. Here we report such an effect in an intriguing regime.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…More subtly, we find that in the presence of the dipolar interactions an algebraic tail is visible in the long-distance decay of correlation functions even in the gapped phase. A similar effect has been reported previously for Ising systems with dipolar interactions [62,63], for longrange interacting p-wave superconductors with Majorana edge modes [64], and for systems with quadratic algebraically decaying interactions it can be proven that in such systems the correlation functions decay with the same exponent as the one of the interaction [65]. Here we report such an effect in an intriguing regime.…”
Section: Introductionsupporting
confidence: 62%
“…Indeed, Hastings and Koma proved this [77] for general short-range interacting spin systems. In contrast, recent theoretical studies have found that long-range interacting systems can have algebraically decaying correlation functions despite the existence of a gap [62,63,65]. In this section we explore this behavior in our model, where especially interesting features emerge.…”
Section: Role Of Dipolar Interactionsmentioning
confidence: 81%
See 1 more Smart Citation
“…[86,87]. While in the early theory studies [85,[88][89][90] spin interactions decaying with the third power of the distance were considered, it was experimentally demonstrated that management of phonon dispersion allows to achieve powers between 0.1 and 3 in the 2D arrays of traps [91]. Recent state of art represents the work on experimental realization of a quantum integer-spin chain with controllable interactions [92].…”
Section: Discussionmentioning
confidence: 99%
“…It would be particularly interesting to follow Refs. 69,[76][77][78][79][80][81][82] and study how all of these spin Hamiltonians and the underlying phase transitions are affected by the long-range nature of the interactions.…”
Section: Applications To Exotic Quantum Magnetismmentioning
confidence: 99%